Journey to the Lost Temple - "Leigh, Susannah" (Usborne Publishing Ltd: London, 2002)
One of an action-packed series of mystery and adventure stories interwoven with plenty of puzzles to solve. Extra clues are given as well as complete answers at the back of the book.
Keywords: Action and adventure fiction